Potential utilization of phenolic acid compounds as anti-inflammatory agents through TNF-α Convertase inhibition mechanisms: a network pharmacology, docking, and molecular dynamics approach - Ekowati, Juni; Tejo, Bimo A.; Maulana, Saipul; Kusuma, Wisnu Ananta; Fatriani, Rizka; Ramadhanti, Nabila Sekar; Norhayati; Novianty, Kholis Amalia; Sulistyowaty, Melanny Ika; Zubair, Muhammad Sulaiman; Yamauchi, Takayasu; Hamid, Iwan Sahrial
Inflammation is a dysregulated immune response characterized by an excessive release of proinflammatory mediators, such as cytokines and prostanoids, leading to tissue damage and various pathological conditions. Natural compounds, notably phenolic acid phytocompounds from plants, have recently garnered substantial interest as potential therapeutic agents to bolster well-being and combat inflammation recently. Based on previous research, the precise molecular mechanism underlying the anti-inflammatory activity of phenolic acids remains elusive. Therefore, this study aimed to predict the molecular mechanisms underpinning the anti-inflammatory properties of selected phenolic acid phytocompounds through comprehensive network pharmacology, molecular docking, and dynamic simulations. Network pharmacology analysis successfully identified TNF-α convertase as a potential target for anti-inflammatory purposes. Among tested compounds, chlorogenic acid (−6.90 kcal/mol), rosmarinic acid (−6.82 kcal/mol), and ellagic acid (−5.46 kcal/mol) exhibited the strongest binding affinity toward TNF-α convertase. Furthermore, phenolic acid compounds demonstrated molecular binding poses similar to those of the native ligand, indicating their potential as inhibitors of TNF-α convertase. This study provides valuable insights into the molecular mechanisms that drive the anti-inflammatory effects of phenolic compounds, particularly through the suppression of TNF-α production via TNF-α convertase inhibition, thus reinforcing their anti-inflammatory attributes.